Successful pilot on Index Based Flood Insurance in Indian state of Bihar, informs policy makers and development agencies for scaling. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Index Based Flood Insurance, by deploying advanced modeling techniques using satellite data, enabled quick insurance payouts to flood-affected farmers over 1,000 households. ) and 100,000 farmers indirectly (learning from participating neighbors) through the crowdsourcing approach.